2000
DOI: 10.1016/s0370-2693(00)00193-3
|View full text |Cite
|
Sign up to set email alerts
|

Texture zeros and weak basis transformations

Abstract: We investigate the physical meaning of some of the "texture zeros" which appear in most of the Ansätze on quark masses and mixings. It is shown that starting from arbitrary quark mass matrices and making a suitable weak basis transformation one can obtain some of these sets of zeros which therefore have no physical content. We then analyse the physical implications of a fourtexture zero Ansatz which is in agreement with all present experimental data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
142
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 16 publications
(20 reference statements)
2
142
0
Order By: Relevance
“…where J is the Jarlskog invariant given by J = ℑm (K us K cb K * ub K * cs ) [11,12]. This CP phase δ presents a discrepancy of about 30.54% with respect to the experimental value δ = 60.16…”
Section: Different Kind Of Ansatzementioning
confidence: 81%
See 2 more Smart Citations
“…where J is the Jarlskog invariant given by J = ℑm (K us K cb K * ub K * cs ) [11,12]. This CP phase δ presents a discrepancy of about 30.54% with respect to the experimental value δ = 60.16…”
Section: Different Kind Of Ansatzementioning
confidence: 81%
“…Furthermore, the Fukuyama-Nishiura ansatz is explored and a new type of ansatz which is controlling the FCNC processes in the top quark sector is proposed. It is worth to mention that phases are explicitly involved since the mass matrices are hermitic, and then they can be written always as M = PM P † , whereM is a real and symmetric matrix and P is a diagonal matrix which contains the phases [11]. For the three family case, a mass matrix ansatz proposed by Fritzsch has been widely discussed [1,10,14], it is…”
Section: Different Kind Of Ansatzementioning
confidence: 99%
See 1 more Smart Citation
“…Through WB transformations, Branco et al [1] show that is always possible to find, at most, three zeros in quark mass matrices with no physical meanings. But, this does not restrict the number of zeros can be found by applying the WB transformation to mass matrices, the case is that the model must be put into a physical context.…”
Section: Introductionmentioning
confidence: 99%
“…A particular texture structure is said to be texture n zero, if the sum of the number of diagonal zeros and half the number of the symmetrically placed off diagonal zeros is n. Interestingly in this approach, it becomes important to investigate when a set of texture zeros result only from the choice of a given basis and when these imply restrictions on fermion mass matrices. Recently 6,7 , it has been shown that some sets of texture zeros are physically insignificant since these can be obtained starting from arbitrary fermion mass matrices by making appropriate unitary transformations also called Weak Basis (WB) transformations. Such transformations allow one to obtain Hermitian fermion mass matrices involving a 'maximum' of three phenomenological texture zeros.…”
Section: Introductionmentioning
confidence: 99%